Ensaios sobre inovação, produtividade e exportação no Brasil - Carvalho, Luciana (2013)
The main aim of this paper is to understand the innovative behavior of Brazilian industrial businesses and verify the impact of innovation on two performance indicators: productivity and capacity for exportation. With the intention of reaching these goals, the thesis is structured into 3 essays. Essay 1 analyzed the behavior of the internal and external factors which influence the innovative activities of Brazilian companies. In order to do this, a theoretical framework was constructed concerning the innovation determinants and, after that, a descriptive analysis was carried out of a group of indicators obtained by special tabling for a sample of innovative and non-innovative businesses, with data from the last three editions of PINTEC Research of Technological Innovation. Essay 2 was an empirical investigation about the relationship between the innovation and production performance of Brazilian companies, by means of two productivity measurements: Work Productivity (WP) and Total Factor Productivity (TFP). To analyze such a relationship, the econometric methodology implemented was based on the estimation of cross-section models given in a panel, with microdata from the last three editions of PINTEC. The aim of Essay 3 was to verify the relationship between innovation and the probability of exporting and the intensity of exportation. The Probit, Bivariate Probit and Ordered Probit probabilistic models were estimated, with microdata from the last three editions of PINTEC. The results found in the three essays point out fragile innovative behavior in the Brazilian industrial sector which results in low productivity gain and low international competitivity, especially in high technological intensity sectors. Spending with R&D is still low in the Brazilian industry, especially when compared with more developed countries. Furthermore, it was found that innovative companies belonging to low and medium intensity industries make more investments in the acquisition of machines and equipment than in R&D activities. On the other hand, the companies in high technological intensity sectors have invested a greater percentage of revenue in spending on R&D. Among the results found it can also be pointed out that the innovation still presents a modest impact on the stimulus for performance in Brazilian industrial businesses. Note that innovation produces incipient impacts on competitivity within the national industry, which is reflected in the lack of the estimated coefficient for the innovation variable in that which refers to the productivity of the companies. Regarding the capacity for exportation, the results were positive and significant, and it can be concluded that innovation increases the propensity to export. However, when analyzing the intensity of exportation the results changed. The indicators of product and process innovation have a negative impact on the exportation intensity of Brazilian companies. One of the possible explanations stems from the fact that Brazilian innovative companies have focused on the internal market, and not on exportation. This evidence corroborates with some studies that discuss the Brazilian industry s loss of competitivity on an international scope, especially in the high technological intensity industry, the main source of product innovation.